Efficacy and safety of mirabegron in children and adolescents with neurogenic detrusor overactivity: An open‐label, phase 3, dose‐titration study. Issue 6 (31st May 2021) - Baka‐Ostrowska, Małgorzata; Bolong, David T.; Persu, Cristian; Tøndel, Camilla; Steup, Achim; Lademacher, Christopher; Martin, Nancy
Abstract: Aims: To evaluate the efficacy and safety of mirabegron in children and adolescents (aged 3 to <18 years) with neurogenic detrusor overactivity (NDO) using clean intermittent catheterization. Methods: In this open‐label, multicenter, baseline‐controlled, Phase III study (NCT02751931), participants received once‐daily mirabegron at an adult dose equivalent of 25 mg. Dose was increased to 50 mg equivalent unless there were safety/tolerability concerns. The primary efficacy endpoint was change from baseline to Week 24 in maximum cystometric capacity (MCC). Secondary urodynamic assessments, Pediatric Incontinence Questionnaire (PIN‐Q), Patient Global Impression of Severity (PGI‐S), Clinician Global Impression of Change (CGI‐C), and Acceptability questionnaires were included. Results: Overall, 86 participants (55 aged 3 to <12 years, 31 aged 12 to <18 years) received treatment; 68 were included in efficacy assessments. A statistically significant increase in MCC from baseline to Week 24 was observed (87.20 ml, 95% confidence interval: 66.07, 108.33; p  < .001); this increase was apparent from Week 4. Significant increases in bladder compliance, bladder volume until first detrusor contraction, average volume per catheterization, maximum daytime catheterized volume and number of dry days per week. Significant decreases in detrusor pressure and number of leakage episodes per day were also observed. Significant improvement in PGI‐S but not PIN‐Q was observed. Most participants reported their condition had either much or very much improved using the CGI‐C. Mirabegron was well tolerated in this population with a profile aligned with that in adults. Conclusions: Mirabegron was effective and well‐tolerated in the treatment of pediatric patients with NDO.